The Effect of Mathematical Connection and Critical Thinking Skills on Mathematical Problem Solving Skills of Vocational School Students - Merry Johanna Purba; Maximus Gorky Sembiring; Pardomuan Sitompul (Journal Research of Social Science, Economics, and Management, 2026)
Mathematical problem-solving skills are an essential competency for vocational school students because they relate to the demands of the world of work that require analysis, reasoning, and proper decision-making. However, the results of observations show that students' problem-solving skills are still low, so a study of the factors that affect them is needed. This study aims to analyze the influence of mathematical connection skills and critical thinking skills on the mathematical problem-solving ability of vocational school students. The study uses a quantitative approach with a correlational ex-post facto type. The research sample amounted to 93 grade XI students of SMK Negeri 1 Doloksanggul who were selected through purposive sampling techniques. The research instruments include mathematical connection tests, critical thinking tests, and problem-solving tests that have been validated and declared reliable. The data were analyzed through simple regression tests and multiple linear regression. The results of the study showed that there was a positive and significant influence of mathematical connection ability on problem-solving ability; there is a positive and significant influence of critical thinking skills on problem-solving skills; and these two variables simultaneously have a significant effect on problem-solving ability. The greatest contribution comes from the ability to think critically. These findings confirm the importance of strengthening mathematical connections and critical thinking in mathematics learning in vocational schools.